Strengthening Village Governance and Safeguarding Human Rights: Legal Perspectives in Comparative Study - Bakarbessy, Andress Deny; Jacob, John Tumba (Jambe Law Journal, 2025)
This study examines the legal frameworks governing village administration and the protection of human rights in Indonesia, Nigeria, and Japan. The legal frameworks analyzed include Villages Law in Indonesia, the Constitution of the Federal Republic of Nigeria, the Local Government Act in Nigeria, and the Local Autonomy Law in Japan. The research adopts a normative legal approach, employing both statutory and comparative methods to examine the regulations, institutional authority structures, and legal principles of those countries. While the three countries acknowledge the significance of village autonomy and human rights protection, they differ markedly in their normative approaches. Indonesia has developed a relatively progressive legal framework; Nigeria continues to grapple with challenges related to legal pluralism; and Japan prioritizes institutional stability and community engagement. The study concludes that the effectiveness of village governance laws is significantly influenced by the clarity of legal norms, the robustness of institutional structures, and the overall coherence of each country’s legal system